Investigating Students’ Perceptions of ChatGPT's Role in Supporting Writing Skills - Mardiansyah; Rulik Setiani (Universitas Islam Negeri Palopo, 2025)
This study investigated second-semester students of the English Education Department at Universitas Muhammadiyah Kotabumi perception of the role of ChatGPT in improving their English writing skills. A descriptive qualitative design was employed, with data collected over 2 days in July 2025 through semi-structured interviews. From a preliminary survey of 25 students, 8 were selected based on their active use of ChatGPT on smartphones for writing activities. Data were analysed using a phenomenological approach to capture students lived experiences and perceptions. The findings revealed that students generally held positive views of ChatGPT, particularly in generating ideas, enriching vocabulary, improving grammar awareness, constructing sentences, and building confidence. ChatGPT was also valued for its accessibility and efficiency, often functioning as a virtual tutor that fostered self-directed learning boosted writing confidence. Despite these advantages, several challenges were identified, such as overreliance on the application, restricted access to premium features, and minor inconsistencies in generated outputs. The study concludes that ChatGPT offers meaningful support for developing writing competence among EFL learners, provided that its use is guided critically and integrated with traditional pedagogical strategies to maintain learners’ creativity, accuracy, and analytical reasoning.